PENGARUH SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG TAPE PISANG SERTA PENAMBAHAN EKSTRAK CASSIAVERA DALAM PEMBUATAN ROTI MANIS - Zarlis .M.S; Fauzan Azima; Sarah Asmar (Jurnal Dinamika Penelitian Industri, 2010)
The research aimed to obtain the optimal additional banana fermented flour and wheat flour on sweet bread an d diversification extract of cassiavera as a flavoring agent and anti microbical, then the storage time in the chamber. The experiment was designed as Factorial Completely Randomized Design witth three stages : The 1st. Making sweet bread by substitution flour,the 2nd. Sweet bread with cassiavera flavour and the 3rd. Stage that the storage time. The result of optimal experiment showed that the substitution 10% of banana fermented flour to wheat folur and 1,25% extract of cassiavera produced the good sweet bread and popular flavoured brad by panelists with the value of tasted are 4.04 (like);color 4,15 (like);flavour 3,8 (like);texture 3.8 (like) maen the composition of sweet bread are : water content 30.37%; ash content 1.48%;protein content 1.03% and carbohydrates 59.50% with good condition until 7 days in storage chamber.